The use of path planning algorithm using edge computing technology in college football training. (14th July 2022) - Zhou, Jun; Zheng, Yingying
The purpose is to study the role and influence of football robots on the actual football training in the current popularity of football robot competition. The theoretical basis and key technologies of the football robot system are deeply studied. The design of the wireless communication subsystem, vision subsystem, decision subsystem and fuzzy PID (port ID) control system of the football robot is completed. The application of edge computing in wireless communication subsystem is discussed. The Immune Algorithm (IA), Particle Swarm Optimisation (PSO) algorithm and Immune PSO (IPSO) algorithm are compared and analysed. IPSO algorithm is used for path planning of football robots. In the comparison of the three algorithms, the convergence stability of the IPSO algorithm is significantly higher than that of IA and PSO algorithm. This research can arouse the common concern and thinking of the scientific and technological circles and the traditional football circles. It is a new field, and a challenge to traditional football. It plays an important role in the research and development of intelligent robot technology and traditional football training, especially the college football team.